Rhabdomyolysis: an American Association for the Surgery of Trauma Critical Care Committee Clinical Consensus Document. Issue 1 (27th January 2022) - Kodadek, Lisa; Carmichael II, Samuel P; Seshadri, Anupamaa; Pathak, Abhijit; Hoth, Jason; Appelbaum, Rachel; Michetti, Christopher P; Gonzalez, Richard P
Abstract : Rhabdomyolysis is a clinical condition characterized by destruction of skeletal muscle with release of intracellular contents into the bloodstream. Intracellular contents released include electrolytes, enzymes, and myoglobin, resulting in systemic complications. Muscle necrosis is the common factor for traumatic and non-traumatic rhabdomyolysis. The systemic impact of rhabdomyolysis ranges from asymptomatic elevations in bloodstream muscle enzymes to life-threatening acute kidney injury and electrolyte abnormalities. The purpose of this clinical consensus statement is to review the present-day diagnosis, management, and prognosis of patients who develop rhabdomyolysis.